If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x+2)+14=2(x+1)
We move all terms to the left:
(3x+2)+14-(2(x+1))=0
We get rid of parentheses
3x-(2(x+1))+2+14=0
We calculate terms in parentheses: -(2(x+1)), so:We add all the numbers together, and all the variables
2(x+1)
We multiply parentheses
2x+2
Back to the equation:
-(2x+2)
3x-(2x+2)+16=0
We get rid of parentheses
3x-2x-2+16=0
We add all the numbers together, and all the variables
x+14=0
We move all terms containing x to the left, all other terms to the right
x=-14
| T2+4t+30=0 | | -47=13-b | | 12y+15=39 | | x^2+2x+4=6x+25 | | 15+3*x=21 | | 43=5x+3 | | 3x+2+72=180 | | m²+m+1=0 | | 3x^2+120x+145=0 | | (X^3+4x^2-32x)/(x+8)=0 | | 3x^2+120+145=0 | | x^2+100x-33600=0 | | 7=4.9+(4.9*n) | | 5x−9=3x+3 | | 8=x÷7x | | (6+y)(5y+9)=0 | | 15+2(5x-4)=37. | | w=4-2 | | 4x−8=3x−8 | | 8x+9=-75 | | 5x-3=2x+4/3 | | -2(3-x=-(x+1) | | 8^24x+8=6^49x+25 | | 6x=9+x | | X^2+y/1.2=11.2 | | 4y-1=2y-1+5y | | 3y+1=2y+21 | | 7n+5=19(n=1) | | 5(t–3)=25 | | X^2+y/1.2=10+y/1.2 | | X^2+y/1.2=10+y/2 | | 2x-10x08=0 |